Pelatihan Merancang Visi dan Misi Sesuai Dengan Perkembangan Siswa Sekolah Dasar dan Kebutuhan Keterampilan Abad 21 - Mahlianurrahman (Faculty of Cultural Studies, Universitas Brawijaya, 2024)
Having an understanding of the formulation of vision and mission is an important thing in producing a vision and mission in accordance with student development and 21st century skills needs. Teachers, principals, and school supervisors in Nagan Raya Regency as participants in the activity strive to produce a vision and mission that is in accordance with these needs. Departing from this, a training was held to design a vision and mission with the aim that each educational unit has a vision and mission in accordance with the development of elementary school students and the needs of 21st century skills. This training was attended by 34 participants and its implementation used the Asset Based Community Development method. Based on the results of the data analysis, it shows that this activity has helped and contributed to improving the understanding and ability of participants in compiling a vision and mission in accordance with the development of elementary school students and the needs of 21st century skills.